Cyanuric acid: Hydrothermal crystal growth and alternative crystallographic description - Sireenart Surinwong (2018)
Single crystals of cyanuric acid in its keto form have been hydrothermally synthesized via the acid catalyzed hydrolysis of 1, 3,5-triazine-2,4,6-triamine triacetic acid. The crystal structure has been solved and refined in a standard monoclinic C2/c which is better preferable than the commonly employed C2/n with b > > 90. The original cell in C2/c are a = 7.9070(13)Å, b = 6.7347(14)Å, c = 9.0788(15)Å, b = 90.794(14)°, V = 483.41(15)Å 3 , R = 0.0473, R w = 0.1288, S = 1.073, and the transformed C2/n cell are a = 7.907Å, b = 6.7347Å, c = 11.9564Å, b =130.602°. Relationships between different crystallographic settings are discussed. The molecular motifs are assembled into two-dimensional layer in (10-1) plane by the 2 4 N-H···O type of hydrogen bonding interactions with graph sets R 2 2 (8) and R 4 4 (16). The molecule shows partial aromatic character, corresponding to the harmonic-oscillator model of aromaticity index of 0.89.